2019
DOI: 10.1152/ajpcell.00278.2018
|View full text |Cite
|
Sign up to set email alerts
|

An inducible knockout of Dicer in adult mice does not affect endurance exercise-induced muscle adaptation

Abstract: The contractile and metabolic properties of adult skeletal muscle change in response to endurance exercise. The mechanisms of transcriptional regulation in exercise-induced skeletal muscle adaptation, including fiber-type switching and mitochondrial biogenesis, have been investigated intensively, whereas the role of microRNA (miRNA)-mediated posttranscriptional gene regulation is less well understood. We used tamoxifen-inducible Dicer1 knockout (iDicer KO) mice to reduce the global expression of miRNAs in adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 34 publications
5
14
0
Order By: Relevance
“…To investigate the role of miRNAs in muscle regeneration, we first generated a mutant mouse with the tamoxifen-inducible disruption of the Dicer gene (iDicer KO). Consistent with our previous data [19], a real-time PCR analysis confirmed the significant reduction in Dicer mRNA expression in the tibialis anterior (TA) muscles of the iDicer KO mice (Figure 1A), whereas the expression levels of the muscle-enriched miRNAs miR-1, miR-133a and miR-26a, and other miRNAs (miR-15b, miR-20a, miR-199a-3p, miR-214, miR-146a, miR-21 and miR-24) were modestly reduced in the iDicer KO mice (Figure 1B).…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…To investigate the role of miRNAs in muscle regeneration, we first generated a mutant mouse with the tamoxifen-inducible disruption of the Dicer gene (iDicer KO). Consistent with our previous data [19], a real-time PCR analysis confirmed the significant reduction in Dicer mRNA expression in the tibialis anterior (TA) muscles of the iDicer KO mice (Figure 1A), whereas the expression levels of the muscle-enriched miRNAs miR-1, miR-133a and miR-26a, and other miRNAs (miR-15b, miR-20a, miR-199a-3p, miR-214, miR-146a, miR-21 and miR-24) were modestly reduced in the iDicer KO mice (Figure 1B).…”
Section: Resultssupporting
confidence: 94%
“…Our data showed that the muscle-enriched miRNAs were highly stable in the TA muscle of the iDicer KO mice (Figure 1B), which is consistent with our previous report [19]. Similarly, recent data on tamoxifen-inducible, skeletal muscle-specific Dicer knockout (HSA-MCM; Dicer fl/fl ) mice showed that the expression levels of miRNAs including miR-1, miR-133a and miR-206 were slightly affected by the Dicer depletion [32].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In previous studies where Dicer1 was conditionally ablated in the skeletal muscle of adult mice, muscle regeneration was impaired after acute injury, but no effect on muscle morphology or function was observed during homeostasis ( Oikawa et al, 2019a ; Oikawa et al, 2019b ; Vechetti et al, 2019 ). An explanation for this difference is that in the Dicer1 conditional knockout experiments miRNA levels were only partially reduced even weeks after Dicer1 ablation, likely reflecting the high stability of these short non-coding RNAs.…”
Section: Discussionmentioning
confidence: 83%
“…In previous studies where Dicer1 was conditionally ablated in the skeletal muscle of adult mice, muscle regeneration was impaired after acute injury, but no effect on muscle morphology or function was observed during homeostasis 24,81,82 . An explanation for this difference is that in the Dicer1 conditional knockout experiments miRNA levels were only partially reduced even weeks after Dicer1 ablation, likely reflecting the high stability of these short non-coding RNAs.…”
Section: Skeletal Musclementioning
confidence: 82%